Level of tuberculosis-related stigma and associated factors in Ugandan communities - Derrick Kimuli; Florence Nakaggwa; Norah Namuwenge; Vincent Kamara; Mabel Nakawooya; Geofrey Amanya; Philip Tumwesigye; Daniel Mwehire; Deus Lukoye; Miriam Murungi; Seyoum Dejene; Jaffer Byawaka; et al. (PLoS ONE, 2025)
Tuberculosis (TB) stigma remains a significant barrier to TB control efforts globally, especially in countries with a high TB burden. Studies about TB stigma done in Uganda so far have been limited in scope and focused on data collected health facilities. In this study we report TB related stigma at community level for the period 2021/2022. We used the 2021/22 Lot Quality Assurance Sampling (LQAS) data from a sample of 33,349 participants across 77 districts, to measure TB stigma determine factors associated. We included demographic characteristics, knowledge and participant perspectives as our study variables. Univariable and multivariate logistic regression analyses were performed to identify factors associated with TB stigma. TB stigma was assessed as a categorical variable (below or above the median) due to the skewness of the data when fitting the scores. The data set had equal proportions of males and females. The largest age group was 20–29 years old (38.47%). Most participants were married (62.94%) and had primary level education (65.80%). The TB stigma scores were assigned on a scale from 0 to 30, with an average score of 21.67 (±8.22) and a median score of 24 (19–28). Overall, 45.48% of participants had TB stigma scores above the median. Variations in TB stigma levels were observed across different districts. Factors associated with higher TB stigma included older age, higher education levels, urban residence, and TB knowledge. To reduce TB stigma and misinformation that can make an impact on TB response, community interventions should balance increasing awareness with minimizing fear. These interventions should be well-rounded and context-specific to address disparities within communities and bolster TB control efforts in the country.